2011
DOI: 10.1016/j.ijnurstu.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a nursing guideline on depression in dementia: A multiple case study on influencing factors

Abstract: Special facilitating factors for the guideline introduction and application seem to be the presence of a local opinion leader and the positive attitudes of relatives. Together they can motivate a nursing team in using the guideline. After a successful introduction of the guideline it's important to focus on its consolidation in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…Studies of complex interventions have shown that influencing factors can occur at several levels [ 23 24 25 ]; the organisational level, the team level, and the individual resident/professional level. For example, some studies [ 25 26 27 28 ] described staff turnover, high workload, concurrent projects, and/or organisational changes as barriers for implementing care innovations. The presence of an opinion leader or support of key persons, and a positive attitude towards change, have been described as facilitating factors in the implementation of an intervention [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of complex interventions have shown that influencing factors can occur at several levels [ 23 24 25 ]; the organisational level, the team level, and the individual resident/professional level. For example, some studies [ 25 26 27 28 ] described staff turnover, high workload, concurrent projects, and/or organisational changes as barriers for implementing care innovations. The presence of an opinion leader or support of key persons, and a positive attitude towards change, have been described as facilitating factors in the implementation of an intervention [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A first step in a systematic implementation process is the identification of barriers and facilitators [ 7 ]. Recent studies have provided some insights in possible barriers and facilitators related to changing the organization of other fields in health care, for example, in the handover of care [ 8 ], case management [ 9 ] and the introduction of nursing guidelines [ 10 ]. However, studies on improving the organization of palliative care are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a major barrier reported was the high turnover of the nursing home workforce [14][15][16][17][18][19]. Moreover, reorganizations, other innovations running at the time of the intervention, absent feeling of relevance by the staff [8,17,18,20] and the culture of the care unit, including attitude towards change, are barriers towards changing current practice [14].…”
Section: Introductionmentioning
confidence: 99%